Prevalence of Hearing Loss Among University Music Students - Comeau, Gilles; Koravand, Amineh; Swirp, Mikael (Canadian Acoustics, 2018)
This study examined the hearing sensitivity of student musicians (N = 53) and non-musicians (N = 54) between the ages of 17 and 31. The two groups were compared for differences in hearing threshold levels, incidences of hearing loss described by pure tone average levels, and incidences of notches at 3, 4 or 6 kHz. Survey data was also used to explore relationships between hearing sensitivity and gender, age, music lesson starting age, musical instruments played, number of years playing that instrument, instrument type, use of hearing protection and personal music device listening time. No significant differences in hearing threshold levels between the two groups was found. Overall prevalence of notches was 1.9% for musicians versus 9.3% for non-musicians using the Niskar (2001) algorithm, or 20.8% for musicians versus 31.5% for non-musicians using the Coles (2000) algorithm. Both algorithms identified more non-musicians with notches, although the difference between the two groups was not significant. Musicians who use hearing protection had significantly more incidences of notches, and there was a weak correlation found between hearing sensitivity and age. The other survey parameters studied showed very little or no relationship with hearing sensitivity. The results do not show any indication that music students are at a higher risk of noise-induced hearing loss than non-music students. Cette étude a examiné la sensibilité auditive d’étudiants musiciens (N = 53) et des non musiciens (N = 54) âgés entre 17 et 31 ans. Les deux groupes ont été comparés pour les différences de seuil auditif, les incidences de la perte auditive décrite par la moyenne des sons purs, et les incidences d’encoches neurosensorielles à 3, 4 ou 6 kHz. Les données ont également été utilisées pour explorer les relations entre la sensibilité auditive et l’âge, le sexe, l’âge du début des cours de musique, les instruments de musique joués, le nombre d’années jouant cet instrument, le type d’instrument, l’utilisation de protection auditive et le temps d’écoute d’appareils de musique personnelle. Aucune différence significative dans les niveaux de seuil auditif entre les deux groupes n’a été trouvée. La prévalence globale d’encoches neurosensorielles était de 1,9% pour les musiciens contre 9,3% pour les non-musiciens utilisant l’algorithme Niskar (2001), et de 20,8% pour les musiciens contre 31,5% pour les non musiciens utilisant l’algorithme de Coles (2000). Les deux algorithmes ont identifié plus de non musiciens avec des encoches, bien que la différence entre les deux groupes ne soit pas significative. Les musiciens qui utilisent la protection auditive ont beaucoup plus d’encoches neurosensorielles, et il y a eu une faible corrélation entre la sensibilité auditive et l’âge. Les autres paramètres étudiés ont montré très peu ou pas de relation avec la sensibilité auditive. Les résultats ne montrent aucune indication que les étudiants musiciens courent un risque plus élevé de perte auditive induite par le bruit que les étudiants non-musiciens.